Pengaruh Model Pembelajaran Rotating Trio Exchange (RTE) terhadap Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti (PAI BP) Siswa Kelas IV di SDN 04 Kubang Putiah Kabupaten Agam - Nelpi Oksa Putri; Deswalantri (YASIN, 2026)
Learning outcomes in Islamic Religious Education and Character Education remain a concern in various studies, but research on the application of the Rotating Trio Exchange (RTE) learning model at the elementary school level remains limited. This study aimed to analyze the effect of the Rotating Trio Exchange learning model on the Islamic Religious Education and Character Education learning outcomes of fourth-grade students at SDN 04 Kubang Putiah. The study employed a quantitative approach with a pre-experimental One-Group Pretest–Posttest Design involving 20 students selected through total sampling. Data were collected using multiple-choice tests administered before (pretest) and after (posttest) the implementation of the learning model. The data were analyzed using descriptive statistics, a normality test, a homogeneity test, a paired-samples t-test, and an N-Gain test. The results showed that the students’ mean score increased from 55.25 on the pretest to 80.45 on the posttest. The test results indicated a significance value of 0.000 (< 0.05), while the N-Gain value of 0.5715 was categorized as moderate. These findings indicate that the implementation of the Rotating Trio Exchange learning model significantly improves learning outcomes in Islamic Religious Education and Character Education. This study strengthens the literature on cooperative learning by emphasizing the importance of active, collaborative, and student-centered learning. Practically, the findings may serve as a consideration for teachers in selecting learning models that promote active participation and improve students’ learning outcomes. Future studies are recommended to examine the implementation of this model across broader subject matter, educational levels, and sample sizes.